Characterization of nimbidiol as a potent intestinal disaccharidase and glucoamylase inhibitor present in Azadirachta indica (neem) useful for the treatment of diabetes. (October 2013) - Mukherjee, Abhishek; Sengupta, Subhabrata
Abstract : Azadirachta indica, used in antidiabetic herbal drugs, was reported to contain α-glucosidase inhibitor. Bioassay guided purification characterized the inhibitor as nimbidiol (a diterpenoid), present in root and stem-bark of the tree. Nimbidiol inhibited intestinal (mammalian) maltase-glucoamylase, sucrase-isomaltase, lactase, trehalase and fungal α-glucosidases. Nimbidiol showed a mixed competitive inhibition on intestinal carbohydrases. IC50, Ki and Ki′ (µM) were 1.35 ± 0.12, 0.08 ± 0.01, 0.25 ± 0.11, respectively, for maltase-glucoamylase (maltotetraose as substrate). Nimbidiol was more potent inhibitor of isomaltase (IC50 0.85 ± 0.035 µM), lactase (IC50 20 ± 1.33 µM) and trehalase (IC50 30 ± 1.75 µM) than acarbose, voglibose, salacinol, kotalanol and mangiferin. Ki and Ki′ values (µM) for intestinal sucrase were 0.7 ± 0.12 and 1.44 ± 0.65, respectively. Development of nimbidiol as an antidiabetic drug appears to be promising because of broad inhibition spectrum of intestinal glucosidases and easy synthesis of the molecule.